Pengaruh Promosi Dan Harga Terhadap Keputusan Berkunjung Pada Objek Wisata - Nainggolan, James Matua; Hidayat, Rahmat (Graha Mitra Edukasi, 2023)
This research aims to determine the influence of promotions and prices on the decision to visit the Tangkahan tourist attraction. This research was conducted at the Tangkahan tourist attraction located on Jalan Kwala Sawit, Namu Sialang Village, Batang Serangan District, Langkat Regency, North Sumatra Province, Indonesia, from January 2021 to March 2021. The variables observed in this research consisted of promotions, prices and the decision to visit. Data was collected through interviews and distributing questionnaires. The population of this study was 1200 visitors to the Tangkahan tourist attraction in March 2021. The sampling technique used was incidental sampling, with a population of 1,200 people and an error rate of 10%, a sample size of 92 people was obtained. Data analysis used a quantitative descriptive method, with the analysis model used being multiple linear regression. The data was processed using the SPSS program, then the research data was tested using validity and reliability tests. Hypothesis testing with coefficient of determination test, simultaneous test and partial test.